COMPARISON OF RETAKE ANALYSIS BETWEEN COMPUTED RADIOGRAPHY AND DIGITAL RADIOGRAPHY - MR.ALEX P PUNNOOSE,; MR. SURESH SUKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
Reject/Retake analysis, one of the key quality control tools in medical imaging field1. It provides detail about unnecessary radiation exposure to patients as well as waste of time3.Results will be useful for training needs and to prepare clinical presentation targeting staffs weakeness1 also to highlight wrong identifications, positioning errors, wrong radiographic technique, bad image processing, and equipment malfunction etc4.The aim of the present research study involves a comparative study between image Retake analysis to compare the outcomes between CR technology and DR technology program in digital environment.